Hedonic Test Analysis and Feasibility of The Selling Price of Cocoa Seed Waste Products in PT XYZ Kulon Progo, Yogyakarta - Sari, Oktavia Nurmalita; Hidayah, Nurul; Rahayu, Wahidah Mahanani (Universitas Ahmad Dahlan, 2021)
Innovative use of waste into herbal beverage products the waste treatment process starts from the stage of roasting cocoa beans, breaking the beans and peeling the skin, sorting, drying, preparation of packaging and materials, filling and mixing, giving silica gel and labelling the expiration date. The raw materials needed are cocoa bean husk, dried cardamom, and cinnamon powder. While the packaging material uses PET plastic bottle packaging. Before the product is marketed, it is necessary to conduct a feasibility analysis of the selling price. The analysis shows that the selling price of chocolate product of Rp. 15,000 is feasible because profit taking is 48% with the selling price per unit more than the cost per unit. The net profit margin of chocolate product of 32.6% means that the company is considered efficient in determining the selling price of its products and successfully controlling costs in it because the NPM figure is > 5%. Hedonic tests were also conducted to determine consumer acceptance of the product through a hedonic test of 20 panelists based on the parameters of color, aroma, taste, and packaging. The hedonic test scale 1 shows that consumers do not like it very much, a scale 2 does not like it, a scale 3 likes it, and a scale 4 likes it very much. The average level of preference for color parameters is 3.58, aroma is 3.31, taste is 3.47, and packaging is 3.84 which indicates that the panelists like these 4 parameters.